Analasis Penerapan Teknologi Traffic Steering SD-WAN Menggunakan Perangkat FortiGate - Nurul Fauziah, Andi Dinda; Nirwana, Hafsah; Litha, Arni; Mahjud, Ichsan (Jurusan Teknik Elektro Politeknik Negeri Ujung Pandang, 2022)
In the current digital transformation era, network providers have long relied on WAN technology to support the business communications of their multi-local companies; however, in terms of infrastructure, cost, and even effectiveness, WAN technology is no longer sufficient to meet the needs and demands of telecommunications customers. In addition, given the magnitude of the company's need for internet network connections, technology is also needed to manage the use of traffic from rental links in the company so that it can optimize bandwidth usage from the link itself. Therefore one of the technological innovations to improve information processes is cloud-based digital innovation such as SD-WAN Traffic Steering technology. In this paper, the SD-WAN network design will be carried out on FortiGate series 50e devices by implementing traffic steering technology which can adjust a link's traffic flow according to the client's wishes. The results of the data obtained indicate that the utilization of ISP links owned by companies (Lintasarta and MNC) has been able to be used optimally, as evidenced by the use of bandwidth on each link successfully used according to the desired settings, where the settings provided have also been adjusted according to parameters of the type of each ISP service so that functionally the existing service link can be used optimally by the compan